1989
DOI: 10.1093/milmed/154.5.250
|View full text |Cite
|
Sign up to set email alerts
|

Hats: Design and Protection from Ultraviolet Radiation

Abstract: An estimated 400,000 non-melanoma skin cancers occur each year. A majority of them will develop on sun-exposed areas of the face, head, and neck. By virtue of having assignments that involve outdoor duty, often in areas of high ultraviolet radiation exposure, military personnel are at increased risk of developing these cancers. Hats provide a means of sun protection; however, some styles are more protective than others. Two styles of hats currently used by the military are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The interviewer observed that most participants wore baseball caps, which provide adequate protection for the face but may leave ears and neck exposed to high levels of UVR. 16,17 According to anecdotal observations made by the interviewer, baseball caps are popular among this sample because farmworkers embed themselves between branches in order to access the fruit and this type of hat is less likely to interfere with this process. In contrast, wide-brimmed hats are obtrusive during the picking process.…”
Section: Discussionmentioning
confidence: 99%
“…The interviewer observed that most participants wore baseball caps, which provide adequate protection for the face but may leave ears and neck exposed to high levels of UVR. 16,17 According to anecdotal observations made by the interviewer, baseball caps are popular among this sample because farmworkers embed themselves between branches in order to access the fruit and this type of hat is less likely to interfere with this process. In contrast, wide-brimmed hats are obtrusive during the picking process.…”
Section: Discussionmentioning
confidence: 99%
“…Actual measurements of sun protection from hats have been made using a radiometer and polysulphone film to measure sun exposure to body sites to assess the performance of hats. Keeling, Kraus, Pathak, and Sober (1989) used a radiometer to compare different styles of hats in field tests and found that a full-brimmed hat offered greater protection from both direct and reflected radiation. Diffy and Cheeseman (1992) studied the protective value of 28 hat styles in relation to UV exposure using polysulphone film in a lab study using nonhuman stationary models for the hats.…”
Section: Design Of Sun-protective Hatsmentioning
confidence: 99%
“…Generally, sun-protective hat research has been limited to simulations using models, usually in a stationary position (Diffy & Cheeseman, 1992) and to specific occupational groups, such as farmers, without addressing specific body positions or sun angles (Lee et al, 1992;Stone, 1999). In addition, previous studies have been limited to studying specific sites on the face and neck for sun protection under various hats (Diffy & Cheeseman, 1992;Keeling et al, 1989;Lee et al, 1992). This study focuses on the area of the body shaded by the hats instead of analysis of face and neck protection from the sun.…”
Section: Design Of Sun-protective Hatsmentioning
confidence: 99%
“…While clothing has been tbe subject of most studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], others have assessed hats [30,31] or shadecloth [32]. Protection from skin cancer by clothing has been assessed in only one study, using a hairless mouse model [33].…”
Section: Histurical Perspectivementioning
confidence: 99%
“…A ceiling of UPF50' was chosen because, firstly, measurement errors increase significantly above that level and, secondly, it provides a safety margin above that needed to protect against the likely maximum daily UVR exposure encountered in Australia (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). As there has been some confusion with SPF numbers, a category description in words will be mandatory along with numbers in the UPF scheme.…”
Section: Current Situation In Australiamentioning
confidence: 99%